Determination of efficient and inefficient units for watermelon production-a case study: Guilan province of Iran - Ashkan Nabavi-Pelesaraei; Reza Abdi; Shahin Rafiee; Iraj Bagheri (Journal of the Saudi Society of Agricultural Sciences)
In this study, data envelopment analysis (DEA) approach was utilized for optimizing required energy and comparing greenhouse gas (GHG) emissions between efficient and inefficient units for watermelon production in Guilan province of Iran. For this purpose, two models including constant returns to scale (CCR) and variable returns to scale (BCC) were applied to determine efficiency scores for watermelon producers. Based on the results, the average of technical, pure technical and scale efficiency was computed as 0.867, 0.957 and 0.906, respectively. Also, 36 and 71 watermelon producers were efficient based on CCR and BCC models, respectively. The total optimum energy required and energy saving were calculated as 34228.21 and 6000.77 MJ ha−1, respectively. Moreover, the highest percentage of energy saving belonged to the chemical fertilizers with 76.62%. The energy use efficiency of optimum units was determined as 1.52 and this rate increased about 18% when compared with existing farms. Also, the energy forms including direct, indirect, renewable and non-renewable energy improved about 15%, 15%, 10% and 15%, respectively. Furthermore, total GHG emissions of efficient and inefficient farms were found to be about 869 and 1239 kgCO2eq. ha−1, respectively. Biocides had the highest difference of GHG emissions between efficient and inefficient farms. Finally, it can be said that applying the DEA approach can reduce total GHG emissions about 371 kgCO2eq. ha−1 for watermelon production in the studied region.